PENGARUH CITRA MEREK, KUALITAS PRODUK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA BRAND NEVADA DI MATAHARI DEPARTEMEN STORE KOTA SURAKARTA - Nugraheni Dama Rasintha; Khabib Alia Akhmad; Esti Dwi Rahmawati (ITB AAS Indonesia Surakarta, 2023)
This study aims to analyze the effect of brand image, product quality, and price on purchasing decisions on the Nevada brand at Matahari Department Store, Surakarta City. This type of research uses quantitative methods. The sampling technique uses a non-probability sampling method (purposive sampling). The sample in this study were consumers of the Nevada brand at the Matahari Department Store who met the criteria, amounting to 100 people. Data was collected using a questionnaire. The results obtained from the t test results for brand image variable, t count > t table (4.814 > 1.894), in conclusion brand image has a positive effect on purchasing decisions. The t test for product quality is t count > t table (6.069 > 1.894), it can be concluded that product quality has a positive effect on purchasing decisions. As for the price, the value of t count > t table (2.119 > 1.894), it can be concluded that the price variable has a positive effect on purchasing decisions. Simultaneously brand image, product quality, and price have a positive and significant effect on purchasing decisions, indicated by a significance F value of 0.000. Keywords: brand image, product quality, price, purchase decision